FIRE SAFETY ISSUES AND WAYS TO SOLVE THEM - M.Doschanov,; O.Yuldosheva, (European Journal of Life Safety and Stability (2660-9630), 2021)
The article provides information on fire safety problems and their causes. There are also suggestions and tasks to address these issues